Edukasi Pola Makan dan Gizi Seimbang pada Lansia Agar Tetap Bugar di Usia Senja: Nutrition and Dietary Education for the Elderly to Stay Fit in Old Age - Widati, Amila; Nurcahyaningtyas, Widya (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Decreased appetite and irregular eating patterns among the elderly can lead to malnutrition or obesity, both of which negatively impact their quality of life. Educational interventions serve as a strategic approach to improve elderly knowledge regarding healthy eating and balanced nutrition. This activity employed a one-group quasi-experimental pretest-posttest design without a control group. It was conducted on January 29, 2025, at the Elderly Health Post (Posyandu Lansia) in Bumi Intan Permai Housing Complex, Sidoarjo. A total of 24 elderly participants were selected purposively. The education was delivered through interactive lectures and group discussions. Evaluation was carried out using pre- and post-education questionnaires to assess knowledge levels related to dietary patterns and balanced nutrition. Data were analyzed descriptively. The results showed that after the educational session, 70% of participants demonstrated a good improvement in understanding the concepts of healthy eating and balanced nutrition. All participants remained until the end of the activity and showed high enthusiasm during the discussion. Nutrition education based on lectures and discussions was effective in improving elderly knowledge about healthy and balanced diets. This activity may serve as a health promotion model in elderly community settings.